Lisu Women Costumes in Nujiang as a CulturalHeritage / Yangyang Zhu ... [et.al] - Zhu, Yangyang; Mohd Rafee, Yakup; Sahari, Faridah (Universiti Teknologi MARA Cawangan Sarawak, 2020)
The Lisu nationality in Nujiang Prefecture is a minority nationality located in the southwest border of China. Its traditional costume is the cultural heritage with local characteristics and the crystallization of Lisu People's wisdom. Most of the previous studies on Lisu costumes were from a macro perspective. However, these studies did not specifically focus on a specific area of Lisu costumes and division in-depth, nor did they conduct research on the differentiation of Lisu costumes in a specific area. This paper discusses the women's costumes of Lisu nationality in Nujiang Prefecture, consisting of the hat, upper garment and lower garment. The objectives of this paper are to explore different Lisu women's costume types in Nujiang region from a microscopic perspective. This study is based on the theory of art anthropology, in which it uses the method of field investigation to sample and collect a number of clothing samples, and inductive method to sort out and classify the clothing types of Lisu nationality in Nujiang, Yunnan Province. The results showed that there are three different types of Lisu costumes in Nujiang of the Lisu Autonomous Prefecture: Lushui type, Lanping type and Fugong type. They were distributed in different regions and presented with different characteristics, which are closely related to the life of the local Lisu minority. It is of great significance for the diversified and sustainable development of Lisu ethnic costumes.